Capitalizing MIM as a platform for mobile business among undergraduates - Che Mahmood, Che Faridah; Omar, Nazihah; Abdullah@ Adnan, Norshaieda (2010)
Mobile Instant Messaging (MIM) or Instant Messaging (IM) via various web-based applications like WeChat, Viber, WhatsApp (WA) and Snapchat have gained much attention. It allows mobile phone users to access instant messaging services right from their smartphones. Majority of researches have focused on MIM in relations to its use in social interaction and as an educational tool. Some valuable insights cited show that the social media in education can be a tool for blended learning. However, studies on MIM’s appeal when used in conjunction with mobile business are still lacking. Various general publications indicate the advantages of mobile business, ranging from the start-up cost, flexibility, mobility up to inventory. The purpose of this study is to explore the realm of MIM usage as a platform for mobile business among undergraduates in Malaysia. Firstly, the main focus is to investigate the uses of MIM for mobile business and secondly, to identify the perceived advantages of MIM as a platform for mobile business. An online questionnaire was designed and randomly distributed to undergraduates who have engaged in mobile business. The questionnaire consists of 3 sections and 15 items. Data were quantitatively analysed using SPSS version 21. Percentages, means, and standard deviations, were used for the analysis. The results show that MIM is frequently used to advertise and sell products most needed by undergraduates. Among the perceived advantages of MIM as platform for mobile business is its cost effectiveness. In addition, undergraduates can easily and conveniently start-up mobile business and generate income simply via a mobile device and a mobile number as it is indeed preferable for reaching general audience.